Should hepatitis B surface antigen positive mothers breast feed?. Issue 10 (October 1985) - de Martino, M; Appendino, C; Resti, M; Rossi, M E; Muccioli, A T; Vierucci, A
Abstract : Breast fed infants may be at greater risk of mother to infant hepatitis B virus infection compared with formula fed infants. We studied 85 infants born to 84 hepatitis B surface antigen positive mothers (only two of whom were hepatitis B e positive), and who had received immunisation against hepatitis B virus. Our results indicate that breast feeding does not increase the risk of developing hepatitis B virus infection in infants born to these mothers if immunisation is carried out.